Faktor-Faktor yang Berpengaruh terhadap Pembentukan Jiwa Kewirausahaan di Lingkungan Mahasiswa STPKat Semarang - Andarweni Astuti (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
The first purpose of this study is to determine the factors that influence the entrepreneurial spirit of individual, psychological and contextual characteristics. The second goal is to verify the attitude and contextual factors that influence students to form an entrepreneurial spirit. The third research objective is to ascertain what STPKat Semarang students own entrepreneurial characteristics are. The research method used is a descriptive method that describes the current phenomena in STPKat St. Fransiskus Assisi, using a quantitative approach and Likert Analysis Method. Some discoveries in this study are 62% of the factors that form the entrepreneurial spirit come from the demographic characteristics of age and status; 72% come from the traits possessed by a person; 82% come from contextual factors in the form of entrepreneurial training and a strong intention to become a Catholic teacher with business(-es) as second income. Attitude and contextual factors influence self-concept by 73%; in terms of interest in entrepreneurship by 88%. Entrepreneurial traits are shown in self-confidence by 82%; increasing results by 83%; taking risks by 75%; leadership by 83%; 77% originality and 79% future-oriented. Self-confidence, focus-on-results and leadership are entrepreneurial traits found in most of STPKat Santo Fransiskus Asisi Semarang students.